Propagation, growth performance and yield of Piper betle L. at different nitrogen and shade levels - Muttaleb, Qusay Abdulhamza (2018)
Piper betle L., an evergreen perennial climber from the family Piperaceae, is an important medicinal plant in Malaysia. Despite its importance, knowledge on its propagation is still lacking. The present study was conducted to explore the feasibility of in vitro and in vivo systems of propagation. Sterilization of explants prior to in vitro procedures was carried out in 20% Clorox for 20 minutes. In vitro culture medium with 1.0 mg/L BAP was the best medium for shoot production. The study also examined in vivo rooting of cuttings and growth performance as affected by different indole 3 butyric acid (IBA) treatments and different nitrogen rates (0, 50 100, 150 kg/ha) and shade levels (0%, 30% and 50 %). Morphological parameters were recorded at 30, 60 and 90 days after planting. Semi-hardwood cuttings treated with 2000 mg/L IBA showed the best rooting performance (100%). Plants were significantly taller in treatment at 50 % shade and 100 kg N /ha. At first (H1), second (H2) and third (last) (H3) harvests, maximum height for each harvest was recorded at 70, 105.67 and 184.67 cm respectively. The number of branches was highest at 26.00 from H3, followed by H2 (10.33) and H1 (6.00). The number of leaves from H1, H2 and H3 harvests were 18.00, 46.33 and 171.00 respectively. The total leaf area recorded from H1, H2 and H3 were 653.17, 4108.28 and 10401.17 cm2 respectively. The fresh weight of leaves were recorded at 18.12 g (H1), 91.07 g (H2) and 185.15 g (H3), while the dry weight of leaves were recorded at 21.55 g (H3) 10. 91 g (H2) and 2.40 g (H1), significantly higher at 30 % shade with 100 kg N/ha. With respect to physiological parameters, photosynthesis (PR) and transpiration (TR) rates and stomatal conductance (SC) increased with increasing light intensity with treatment at 30 % shade and 100 kg N/ha giving the highest PRof 10.13 μmol CO2 / m2 /s, SC 0.13 mol/m2/s dan TR 1.60 μmol/m2/s. Chlorophyll content (a and ab) did not show any significant difference in the 30% and 50 % shade levels (1.55 and 1.49 mg/cm2) but was highest at 100 kg N/ha (1.76 mg/cm2). Chlorophyll b was highest at 50% shade which suggests that chlorophyll-a biosynthesis in relation to chlorophyll-b was significant in low light intensity. Total phenolic content (TPC) (highest at 1.19 mg (GAE)/g), total flavonoid content (TFC) (highest at 128.13 mg Quercetin/g) and antioxidant activities (DPPH) (highest at 85.15%) and FRAP 7.87 μmol Fe(ll)/g dry) were highly significant in the control treatment.